THE IMPACT OF ETHICAL LEADERSHIP ON FIRM PERFORMANCE IN BAHRAIN: ORGANIZATIONAL CULTURE AS A MEDIATOR - Tariq Tawfeeq Yousif Alabdullah; Amal Jasim Mohamed AL-Qallaf (Transpublika Publisher, 2023)
In many industries, especially in the quick-paced technological world, ethical leadership (EL) has become a crucial driver of company financial performance and competitive advantage. Senior management's behavior is vital in influencing organizational decision-making and accomplishing pre-set objectives. This study focuses on the organizational culture's mediating function as it explores the relationship between ethical leadership and the firm financial performance of non-financial enterprises in Bahrain. This study explores the complex relationship between behavioral leadership, organizational culture, and firm financial performance using a theoretical conceptual framework approach. Bahrain is the right setting for this inquiry because of its vibrant business community and wide variety of non-financial businesses. The importance of ethical leadership in overcoming obstacles while preserving ethical standards is influenced by the nation's advantageous geographic location, encouraging government policies, and technological investments. The main goal of the current study is to clarify how senior management's ethical leadership practices affect the financial performance of non-financial enterprises in Bahrain while taking organizational culture's mediating function into account. The study advances knowledge of how ethical leadership, organizational culture, and firm financial performance interact within Bahrain's socio-cultural and economic setting by investigating this interaction. This study contributes to the body of knowledge on ethical leadership in Bahraini non-financial organizations through thorough investigation guided by the theoretical framework. The importance of ethical leadership in overcoming obstacles while preserving ethical standards is influenced by the nation's advantageous geographic location, encouraging government policies, and technological investments. The main goal of the current study is to clarify how senior management's ethical leadership practices affect the financial performance of non-financial enterprises in Bahrain while taking organizational culture's mediating function into account. The study advances knowledge of how ethical leadership, organizational culture, and financial performance interact within Bahrain's socio-cultural and economic setting by investigating this interaction. This study contributes to the body of knowledge on ethical leadership in Bahraini non-financial organizations through thorough investigation guided by the theoretical framework. It offers understanding into how organizational culture and ethical leadership practices affect their financial performance. The research findings should have repercussions for academics and professionals, improving knowledge of behavioral leadership and the mediating function of corporate culture for accomplishing organizational success. By analyzing the effects of ethical leadership within the specific context of non-financial enterprises in Bahrain, this study will advance knowledge. The complicated relationships between ethical leadership, organizational culture, and financial performance are further understood by recognizing the mediating function of organizational culture. The originality of the current study is in providing a springboard for additional investigation into ethical leadership and its connection to corporate culture across many fields and industries. The current study's anticipated consequences include how its findings might be applied to improve leadership development, talent recruitment, and the creation of a healthy organizational culture. Organizations can link their business goals with ethical principles and gain a competitive advantage through the promotion of ethical leadership practices and the development of a supporting culture.